Back‐flow ripples in troughs downstream of unit bars: Formation, preservation and value for interpreting flow conditions. Issue 7 (27th April 2015) - Herbert, Christopher M.; Alexander, Jan; Martínez de Álvaro, María J.
Abstract: Back‐flow ripples are bedforms created within the lee‐side eddy of a larger bedform with migration directions opposed or oblique to that of the host bedform. In the flume experiments described in this article, back‐flow ripples formed in the trough downstream of a unit bar and changed with mean flow velocity; varying from small incipient back‐flow ripples at low velocities, to well‐formed back‐flow ripples with greater velocity, to rapidly migrating transient back‐flow ripples formed at the greatest velocities tested. In these experiments back‐flow ripples formed at much lower mean back‐flow velocities than predicted from previously published descriptions. This lower threshold mean back‐flow velocity is attributed to the pattern of velocity variation within the lee‐side eddy of the host bedform. The back‐flow velocity variations are attributed to vortex shedding from the separation zone, wake flapping and increases in the size of, and turbulent intensity within, the flow separation eddy controlled by the passage of superimposed bedforms approaching the crest of the bar. Short duration high velocity packets, whatever their cause, may form back‐flow ripples if they exceed the minimum bed shear stress for ripple generation for long enough or, if much faster, may wash them out. Variation in back‐flow ripple cross‐lamination has been observed in the rock record and, by comparison with flume observations, the preserved back‐flow ripple morphology may be useful for interpreting formative flow and sediment transport dynamics.